1984
DOI: 10.1007/bf00334103
|View full text |Cite
|
Sign up to set email alerts
|

Selective transduction of recombinant plasmids with cloned pac sites by Salmonella phage P22

Abstract: Recombinant plasmids having PstI fragments of P22 DNA inserted in the vector pBR322 can be transduced efficiently by Salmonella phage P22, irrespective of the cloned phage sequences. When the rec function of the donor cells and the corresponding recombination system erf of the infecting phage are simultaneously inactivated, only plasmids containing the P22 pac site can be transduced. By this selective, generalized transduction an EcoRV DNA fragment of the P22 related phage L has been identified that carries a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 23 publications
3
27
0
Order By: Relevance
“…pRSM14 was found to carry cyslH on a 4.9-kb insert, and pRSM15 carried the entire cysJIH region on a 7.8-kb fragment which overlapped both ends of the pRSM14 insert. The restriction map of this region (not shown) corresponded to that previously found for the cysJIH region cloned from S. typhimurium LT7 (J. Ostrowski and N. M. Kredich (20) and demonstrated by Schmidt and Schmieger for plasmids containing cloned sequences of P22 (22). In agreement with these investigators, we found that P22HT lysates from the wild type carrying either pBR322 (4.4 kb), pRSM3 (7.1 kb), or pRSM15 (12.3 kb) gave fragments could account for this discrepancy by giving large inserts derived from fragments too small to constitute a complete gene.…”
Section: Methodssupporting
confidence: 75%
“…pRSM14 was found to carry cyslH on a 4.9-kb insert, and pRSM15 carried the entire cysJIH region on a 7.8-kb fragment which overlapped both ends of the pRSM14 insert. The restriction map of this region (not shown) corresponded to that previously found for the cysJIH region cloned from S. typhimurium LT7 (J. Ostrowski and N. M. Kredich (20) and demonstrated by Schmidt and Schmieger for plasmids containing cloned sequences of P22 (22). In agreement with these investigators, we found that P22HT lysates from the wild type carrying either pBR322 (4.4 kb), pRSM3 (7.1 kb), or pRSM15 (12.3 kb) gave fragments could account for this discrepancy by giving large inserts derived from fragments too small to constitute a complete gene.…”
Section: Methodssupporting
confidence: 75%
“…Lytic Yersinia phages from environmental sources have been shown to perform generalized transduction of small plasmids (19). Plasmid transduction with phage P22 was also reported either by homologous recombination between phage DNA and plasmid DNA that harbored P22 sequences (cointegrate formation), or when a pac-like sequence was present on a plasmid that can be packaged in a headful mechanism from concatemeric DNA (40). It seems feasible to develop PY100 phage derivatives that can be used for transduction.…”
Section: Resultsmentioning
confidence: 99%
“…Two ml of the phage lysate was mixed with 5.4 ml of phage dilution buffer (50 mM Tris-HCI (7.5), 0.15 M NaCI, 5 mM MgS0 4 ) containing CsCl (0 = l.740), and the density was finally adjusted to 1.500. Centrifugation was done in a Hitachi RBS swing rotor at 19000 rpm for 27 hours (4°C).…”
Section: Plasmids With Inserted Cohesive End Sites (Cos) Of Phages Sumentioning
confidence: 99%